THE ROLE OF EFFECTIVE PRINCIPAL LEADERSHIP AND ORGANIZATIONAL CULTURE IN IMPROVING TEACHER PERFORMANCE AT SENIOR HIGH SCHOOL - Uyu Wahyudin; Saepudin Saepudin (LPSDI Bina Patria, 2023)
The purpose of this study is to examine the relationship between the leadership role of an effective principal and organizational culture in terms of improving teacher performance. Effective principal leadership plays a critical role in enhancing teacher performance, as does a strong organizational culture that reflects the school's values. The sampling technique used was cluster random sampling, with a sample size of 175 people. A questionnaire was distributed to teachers at State Senior High Schools in West Java, Indonesia, as part of the research technique. To collect the necessary data, the questionnaire is completed following the statement items, using a Likert scale with five alternative responses. The data were analyzed using SEM was estimated using the SmartPLS (Smart Partial Least Squares) software. It was discovered that effective principal leadership exists to have a positive and significant effect on the performance of teachers. Additionally, this study demonstrates the critical role of organizational culture in enhancing teacher performance. These findings point the way forward in terms of enhancing the quality of school leadership, as well as the effectiveness of organizational culture, to boost teacher performance.